Classical and Microwave-Assisted Synthesis of Substituted- Dihydroxy-imidazolidine-2-thiones Compounds - Pıhtılı, Güzin; Tuncer, Hülya (Hacettepe Üniversitesi, 2017)
In this study, N-N’-disubstitued thiourea and N-N’-disubstituted-4,5-dihydroxy-2-imidazolidine-2-thione were prepared through the reaction of suitable primary aromatic amines with phenylisothiocyanate and 4-met- hoxyphenylisothiocyanate. The synthesis of N-N’-disubstitued thiourea were carried out by classic methods. Later, the acid-catalyzed cyclocondensation in refluxing acetonitrile of aqueous glyoxal and led to the formati- on of the corresponding N,N’-disubstitued-4,5-dihydroxyimidazolidin-2-thiones. Thiourea derivatives were pre- pared both classical method and microwave assisted synthesis. Microwave-assisted reaction was performed in temperature and pressure control devices with the atmospheric pressure environment. The structures of synthesized organic compounds were characterized by FT-IR and 1HNMR spectroscopy.

B u çalışmada, aromatik aminlerin, fenilizotiyosiyanat ve 4-metoksi-fenilizotiyosiyanat ile tepkimesi ile, N-sübstütiye-N’-feniltiyoüre ve türevleri sentezlendi. Daha sonra sentezlenen bu bileşikler, asidik ortamda sulu glioksal çözeltisi ile reflaks edildi ve N,N’-disübstütiye-4,5dihidroksi-imidazolidin-2-tiyon bileşikleri sentezlendi. N-sübstütiye-N’-feniltiyoürenin sentezi, geleneksel ısıtma yöntemi kullanılarak gerçekleştirildi. Tiyoüre türevlerinin sentezi hem klasik yöntem hem de mikrodalga destekli sentez yöntemiyle yapıldı. Mikrodalga destekli tepkimeler, sıcaklık ve basınç kontrollü cihazla atmosfer basınçlı ortamda gerçekleştirildi. Tüm ürünler, FT-IR ve 1H-NMR spektroskopik analiz yöntemleri ile karakterize edildi
Sübstütiye Dihidroksi-imidazolidin-2-tiyon Bileşiklerinin Klasik ve Mikrodalga Destekli Sentezi